Review of Islamic Law on the Lease of Agricultural Land Payment by Harvest (Case Study of Sungai Gampa Asahi Village) - Nasrulllah; Prof. Dr. H. Ahmadi Hasan; Farihatni Mulyati, M.Ag; Heny Handayani; Putri Ramadanti; Muhammad Saifullah; Nur Rika (Sharia Journal and Education Center Publishing, 2023)
ABSTRACT This study discusses